2020
DOI: 10.18332/tid/119115
|View full text |Cite
|
Sign up to set email alerts
|

Mothers’ prenatal tobacco smoke exposure is positively associated with the occurrence of developmental coordination disorder among children aged 3–6 years: A cross-sectional study in a rural area of Shanghai, China

Abstract: INTRODUCTION Prenatal tobacco smoke exposure is a potential risk factor for developmental coordination disorder (DCD) in children, but evidence on the relationship between DCD in children and tobacco smoke exposure in women is limited in China. We conducted a cross-sectional study to understand the prevalence of prenatal tobacco smoke exposure among mothers and the prevalence of DCD among children and to explore if mothers' prenatal tobacco smoke exposure is positively associated with the occurrence of DCD amo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 35 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…There are significant discrepancies in the relationship between smoking and the development of PIH [10][11][12][13]. Establishing these relationships is important because it is estimated that around a quarter of the population in the European Region smokes [14,15], and maternal smoking is the most prevalent preventable cause of pregnancy complications such as neonatal morbidity, low birthweight, and premature delivery [16]. Many studies have shown that smoking during pregnancy (paradoxically) reduces the risk of PE.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are significant discrepancies in the relationship between smoking and the development of PIH [10][11][12][13]. Establishing these relationships is important because it is estimated that around a quarter of the population in the European Region smokes [14,15], and maternal smoking is the most prevalent preventable cause of pregnancy complications such as neonatal morbidity, low birthweight, and premature delivery [16]. Many studies have shown that smoking during pregnancy (paradoxically) reduces the risk of PE.…”
Section: Introductionmentioning
confidence: 99%
“…Tobacco smoke contains more than 7000 chemicals, among them various toxic and carcinogenic and cocarcinogenic substances [8,9,11,12,[17][18][19][20]. Smoking has been shown to trigger inflammatory processes and to increase oxidative stress, as well as to reduce placental flows [16,17]. On the other hand, the study by Laule et al indicates that nicotine can have anti-inflammatory effects through the α7-nAChR (acetylcholine receptor subunit) and inhibition of pro-inflammatory cytokine production, which may attenuate hypertension caused by placental ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…Some risk factors for CHDs [27], such as maternal chronic conditions and habits, history of adverse outcomes in previous pregnancies, and the treatment for gestational thyroid disease, were not collected in the present study. However, we do not think the lack of these factors in the present study would significantly shake the results since the population-attributable fraction of these factors was low (1.2%), the large sample size in the present study had enough power to ensure robust associations, and pregnant women rarely smoke (<1.0%) in Shanghai, China [28]. Finally, although the findings were powered by a large sample of women and the missingness analyses showed consistent results, we acknowledge a potential selection bias induced by a certain percentage of women who were lost to follow-up.…”
Section: Discussionmentioning
confidence: 65%
“…The findings reported in this large-scale population retrospective cohort study are consistent with previous research with smaller sample sizes. A single center study ( N = 8,586) in Shanghai, China, found that the occurrence of DCD among children was positively associated with prenatal SHS exposure among mothers (OR = 1.77; 95% CI: 1.47–2.14) ( 24 ). Furthermore, a cross-sectional examination of 122 children in Niagara, Ontario, Canada, suggested that exposure to SHS during pregnancy increases the risk of DCD in children ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…Children with DCD are characterized by significantly impaired function in motor coordination; however, the etiology of the disorder is still largely unclear. An earlier study with a small sample ( N = 122) ( 23 ), as well as another study involved 8,586 children in Shanghai, China, looking at maternal exposure to first- and second-hand smoking ( 24 ), both reported a lower risk of DCD in children whose mothers were not exposed to tobacco smoke during pregnancy. Nevertheless, there is no large-scale specific research on the relationship between prenatal SHS and DCD to confirm the impact of prenatal SHS exposure on off-spring neurodevelopment.…”
Section: Introductionmentioning
confidence: 99%